2012
DOI: 10.1530/joe-12-0016
|View full text |Cite
|
Sign up to set email alerts
|

Role of testosterone and photoperiod on seasonal changes in horn growth and sperm variables in the Iberian ibex: a model for polygynous wild bovids

Abstract: This work examines the effect of testosterone secretion and photoperiod on seasonal changes in horn growth and sperm variables in the Iberian ibex (Capra pyrenaica), here used as a model for polygynous wild bovids. The hypothesis that high levels of testosterone provide an endocrine signal that inhibits horn growth in autumn was tested by assessing the effect of cyproterone acetate (CA), an anti-androgen, administered in October -coinciding with the period of natural increases in plasma testosterone concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Although the effect of nutrition and photoperiodicity spe-cifically on rhamphothecal growth is generally not known, support for these mechanisms can be found for other keratin-based structures. The effect of ambient temperature on nutritional status has been demonstrated in affecting the growth rate of horns in sheep (Hoefs and Nowlan 1997;Giacometti et al 2002) and photoperiod has been implicated in breeding season increases in horn growth as well (Santiago-Moreno et al 2012). Seasonal variation in growth rate has been documented in bovine hoofs, another keratinized structure (Hahn et al 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effect of nutrition and photoperiodicity spe-cifically on rhamphothecal growth is generally not known, support for these mechanisms can be found for other keratin-based structures. The effect of ambient temperature on nutritional status has been demonstrated in affecting the growth rate of horns in sheep (Hoefs and Nowlan 1997;Giacometti et al 2002) and photoperiod has been implicated in breeding season increases in horn growth as well (Santiago-Moreno et al 2012). Seasonal variation in growth rate has been documented in bovine hoofs, another keratinized structure (Hahn et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…) and photoperiod has been implicated in breeding season increases in horn growth as well (Santiago‐Moreno et al. ). Seasonal variation in growth rate has been documented in bovine hoofs, another keratinized structure (Hahn et al.…”
Section: Discussionmentioning
confidence: 99%
“…The two treatments modified the plasma testosterone concentration as expected 33 -modifications that were associated with changes in sperm cryoresistance. The rapid reduction in blood plasma testosterone levels after CA treatment was similar to that observed in white-tailed deer, 42 fallow deer, 23 and domestic goat.…”
Section: Discussionmentioning
confidence: 63%
“…However, the results are controversial. For example, some researchers have reported that SARS-CoV-2 was not detected in the male reproductive tract, [25][26][27][28][29][30][31][32][33][34] while others reported that SARS-CoV-2 RNA was found in the semen or testes of COVID-19 patients. 35,36 There are also unknown factors regarding COVID-19 and male reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…The Iberian ibex has been used as a model for reproductive studies in wild caprine species (Santiago-Moreno et al, 2012). Hence, this methodology for sperm morphometric assays is recommended for other related wild species such as the Alpine ibex (Capra ibex), Nubian ibex (Capra nubiana), chamois (Rupicapra pyrenaica), etc.…”
Section: Tablementioning
confidence: 99%